2020
DOI: 10.1002/yea.3538
|View full text |Cite
|
Sign up to set email alerts
|

Closely related budding yeast species respond to different ecological signals for spore activation

Abstract: Spore activation is one of the most important developmental decisions in fungi as it initiates the transition from dormant and stress‐resistant cells to vegetative cells. Because in many species mating follows spore activation and germination, signals that trigger this developmental transition can also contribute to species reproductive barriers. Here, we examine the biochemical signals triggering spore activation in a natural species complex of budding yeast, Saccharomyces paradoxus (lineages SpA, SpB, SpC an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…This transition involves multiple changes in cellular state [ 18 ], including the reactivation of multiple metabolic reactions. Although the precise nutrient stimuli that drive germination is dependent on ecological contexts, a carbon source such as glucose is typically an essential signal [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This transition involves multiple changes in cellular state [ 18 ], including the reactivation of multiple metabolic reactions. Although the precise nutrient stimuli that drive germination is dependent on ecological contexts, a carbon source such as glucose is typically an essential signal [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the yeast species, such signals include the presence of different carbon sources, temperatures, etc. A paper by Plante and Landry (2020) found that although dextrose is sufficient to trigger spore germination in S. cerevisiae , in certain wild lineages of Saccharomyces paradoxus , dextrose is necessary but not sufficient to trigger spore formation, and inorganic phosphate is also required for the process. These findings highlight the differences in environmental conditions required for two closely related budding yeast species to undergo spore germination.…”
mentioning
confidence: 99%